A Rare Case of Chylothorax Manifestation of Gorham’s Disease, Lymphangioma and Tuberculosis - Agil Dananjaya; Setyawan, Ungky; Putra, Ngakan; Erawati, Dini; Isharanto, Artono; Norahmawati, Eviana; Irmansyah, Istan (Universitaas Brawijaya, 2022)
Background: Chylothorax is a rare condition caused by accumulation of chyle in the pleural cavity (2-3%). More rare causes are Gorham's disease and tuberculosis Case: A 31-year-old male complained of swelling left arm and shortness of breath with recurrent pleural effusion. Pleural fluid analysis showed chylous. Bone survey showed osteolytic lesions of multiple bones as Gorham's disease. Thoracic CT showed left lung mass, atelectasis, massive fluidothorax, ipsilateral supraclavicular lymphadenopathy, destructive left scapula. Needleaspiration of left humerus revealed lymphangioma. Expert Mtb-Rif examination revealed Mtb detected. We assessed Gorham'sdisease, lymphangioma and lung tuberculosis with complication recurrent chylothorax and was treated anti-tuberculosis, anti-osteolytic and thorax catheter insertion. Conclusion: Difficult and rare case of chylothorax in one patient with Gorham’s disease and tuberculosis, is a poor prognosis. Keywords: Chylothorax, Gorham's Disease, Tuberculosis